Perkembangan dan Pelaksanaan E-Money di Malaysia, Pakistan dan Afghanistan - Fadhil, Muflihul; M, Mukhlis; S, Syahpawi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine the development and implementation of e-money in Malaysia, Pakistan and Afghanistan. This research includes literature study, a method of collecting data by browsing files, internet websites, documents and information related to the research object including relevant books. The results of this research are that according to the Bank for International Settlement (BIS), electronic money is an amount of money that is stored in electronic media owned by a person. E-money is experiencing development in various countries. In Malaysia, E-Money is issued under the name EMI (Electronic Money Publisher) which is tasked with issuing Sharia-based electronic money. On December 30 2022, the Central Bank of Malaysia, Bank Negara Malaysia (BNM) issued several E-Money such as Wise, Touch 'n Go, GrabPay, MAE, BigPay, Boost, GoPayz, WeChat Pay, AliPay, Merchantrade Money. In Pakistan in 2009 Telenor Microfinance Bank published EasyPasia which is the most popular mobile wallet for the people of Pakistan. In 2012 Pakistan launched Jazzcash (a digital payment and branchless banking service) introduced as 'Mobicash' and partnered with Mobilink Microfinance Bank. In 2013, UPaisa was established, a joint venture between U Microfinance bank & Ufone Company, a mobile wallet that offers convenient transactions. In Pakistan there is also Sapapay (Exclusive Payment Solution in Pakistan) which is widely used by Pakistani expatriates. In Afghanistan in 2016, Sanzar Kakar founded HesabPay, HesabPay became the first and only interoperable digital payment platform in Afghanistan, first built as a solution to the humanitarian aid crisis, organizations used the HesabPay platform for payments by sending funds directly to 400 people. districts and 34 provinces in Afghanistan.